KEMAMPUAN PEDAGOGICAL CONTENT KNOWLEDGE GURU SMK DALAM PENYUSUNAN RPP ESTIMASI BIAYA KONSTRUKSI - Heri Franata Sitorus; Asri Widowati; Doni Dwi Hartanto; Willy Ihsan Rizkyanto; Anni Zahara Putri; Defris Hanindya Edwiyan Pradana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Pedagogical Content Knowledge (PCK) is a key competence in vocational education, as it requires the integration of subject matter mastery and contextualized pedagogical strategies. In the subject of Construction Cost Estimation (CCE), the quality of Lesson Plan development is strongly determined by teachers’ PCK ability. This study aims to describe the PCK ability of CCE teachers in public vocational high schools in the Special Region of Yogyakarta in developing Lesson Plans, viewed from teacher certification status and school accreditation level. This study employed a quantitative descriptive approach involving 16 CCE teachers from A- and B-accredited public vocational schools. Data were collected using a validated and reliable PCK questionnaire (Cronbach’s Alpha = 0.82) and supported by classroom observations. Data analysis was conducted using descriptive statistics and an independent samples t-test. The results show that the PCK ability of CCE teachers is generally categorized as good (87.50%). The mean score of teachers in A-accredited schools was 73.33, while those in B-accredited schools obtained a mean score of 72.50. Certified teachers achieved a mean score of 73.63, whereas non-certified teachers scored 72.00. Statistical testing indicates no significant differences in PCK ability based on school accreditation (Sig. = 0.863) or teacher certification status (Sig. = 0.716). These findings suggest that the relatively equal distribution of PCK ability may be influenced by collaborative practices within the Subject Teacher Forum (MGMP). Strengthening teachers’ PCK should therefore focus on developing more contextual and innovative instructional strategies rather than merely standardizing lesson planning documents. ABSTRAK Pedagogical Content Knowledge (PCK) merupakan kompetensi kunci dalam pembelajaran vokasi karena menuntut integrasi antara penguasaan materi dan strategi pedagogis yang kontekstual. Pada mata pelajaran Estimasi Biaya Konstruksi (EBK), kualitas Rencana Pelaksanaan Pembelajaran (RPP) sangat ditentukan oleh kemampuan PCK guru. Penelitian ini bertujuan untuk mendeskripsikan kemampuan PCK guru EBK di SMK Negeri Daerah Istimewa Yogyakarta dalam menyusun RPP, ditinjau dari status sertifikasi pendidik dan akreditasi sekolah. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan subjek 16 guru EBK dari SMK Negeri berakreditasi A dan B. Data dikumpulkan melalui angket PCK yang tervalidasi dan reliabel (Cronbach’s Alpha = 0,82) serta observasi pembelajaran. Analisis dilakukan menggunakan statistik deskriptif dan uji independent t-test. Hasil penelitian menunjukkan bahwa kemampuan PCK guru EBK berada pada kategori baik (87,50%), dengan rata-rata skor sekolah berakreditasi A sebesar 73,33 dan akreditasi B sebesar 72,50. Guru bersertifikasi memiliki rata-rata 73,63, sedangkan guru belum bersertifikasi 72,00. Uji statistik menunjukkan tidak terdapat perbedaan signifikan kemampuan PCK berdasarkan akreditasi sekolah (Sig. = 0,863) maupun status sertifikasi pendidik (Sig. = 0,716). Temuan ini mengindikasikan bahwa pemerataan kemampuan PCK dipengaruhi oleh kolaborasi melalui MGMP. Penguatan PCK perlu diarahkan pada pengembangan strategi pembelajaran EBK yang lebih kontekstual dan inovatif, tidak hanya pada keseragaman perangkat pembelajaran.